South African traditional healers' perceptions and treatment of the symptoms of depression - Augustine, Daniella Joan (Rhodes University, Faculty of Humanities, Department of Psychology)
While depression is experienced worldwide, the World Health Organization indicated that over 80% of this disease burden is found in low- and middle-income countries, with 16% of depressive disorder cases being found in Africa. Specifically, in South Africa, the lifetime prevalence of major depressive disorder is 9.7%. Research conducted on traditional healing estimates that as high as 80% of black individuals in South Africa choose to consult traditional healers. Although there was initial consensus that the use of traditional healers reflected a lack of access to alternative resources, more recent research has however indicated that traditional healers are consulted even when psychiatric facilities and medication are available. Research has illustrated that many patients that chose to consult traditional healers do so as a result of their shared beliefs, and traditional healers' ability to understand the cultural frameworks underlying illness. The current study investigated how traditional healers in the Eastern Cape perceive and treat phenomena currently understood as the symptoms of depression and how these understandings can be incorporated into collaborations between Western medicine and traditional healing practice. A qualitative research design was used to examine the perspectives and treatment methods of isiXhosa traditional healers in the Eastern Cape. Four healers participated in the study. Key findings indicated that there is no single cause or definition of the phenomenon of depression by healers. Causality is greatly attributed to spiritual causes and ancestors play a key role in guiding the diagnosis and multiple treatment interventions employed by healers to treat the experience of depression. Finally, all traditional healers expressed a willingness to collaborate and work with the Western healthcare system, however, they indicated a strong need for greater recognition as a valid healthcare system.
Keywords: Depression, Mental -- South Africa; Mental illness -- South Africa; Depression, Mental Treatment; Traditional healers of -- South Africa; Symptoms; Depression, Mental Social aspects